Highly substituted medium-sized ring-fused azocinoquinoline scaffolds by post-Ugi-4CR reductive carbopalladation cyclization - Janatian Ghazvini, Helya; Rominger, Frank (The journal of organic chemistry, 2019)
A concise synthesis of quinoline-fused eight-membered rings from simple starting materials is described. Reductive cyclo-carbopalladation of suitable Ugi-4CR substrates as a key step leads to the regio- and diastereoselective formation of 1,2-dihydroazocino[4,3-b]quinolin-3-ones under mild reaction conditions with good yields in short reaction time.